A Socio-Legal Study On The Adequacy Of Law In Combatting Baby Dumping In Malaysia - Mazbah Termizi
Today, baby dumping is very common in Malaysia, and the laws relating to it are questionable. Driven by the above concerns, the study's objective was to assess the effectiveness of the law on the criminal penalties of baby dumping in Malaysia and discussion from a social perspective to strengthen the findings. This study is based on analysis of the law relating to the baby dumping from the Malaysian Penal Code, the Child Act 2001 and international law, and previous cases to find the lacuna of the laws and compare with other countries' laws. By contrast, alternatives to the sentence of baby dumping are discussed to address this issue, either through the method of baby hatch or through general defense reasons, such as insanity, post-partum psychosis and so on. Given that Malaysia has two legal systems, this study also covers Shariah advocates on baby dumping issues. This thesis also opts for qualitative research method, content analysis and interviews. By analysing the laws of several countries, it is proposed that several approaches be taken to improve the law on baby dumping. New laws may be introduced to reduce these cases in Malaysia in the future. The findings of this study found that not only does the law need to be streamlined to curb the issue of baby dumping in Malaysia, but holistic approaches need to be strengthened as well. The recommendation is that to improvise the Penal Code in terms of punishment towards the baby dumping offenders and at the same time to provide the alternatives of punishment.